Strategi Pengembangan Produk BSI KUR (Kredit Usaha Rakyat) Mikro di BSI KCP Lamongan Pasar Babat - Muhamad Malik Azhar; Ahmad Afan Zaini (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2022)
BSI KCP Lamongan Pasar Babat is an Islamic financial institution that manages funds through channeling funds to the public in the form of financing. A company does not escape taking action to develop new products or existing products so that there is no decrease in business growth with a decreasing level of consumer desire. Therefore, to prevent this from happening, BSI KCP Lamongan Pasar Babat took product development strategy actions. The type of research used in this writing itself uses a qualitative approach. That is a type of research that describes a state of an object or event that presents data in the form of brief descriptions, charts, and the like. The method used in collecting data in this study uses interviews, observation, and documentation. MICRO KUR product development strategy AT BSI KCP Lamongan Pasar Babat Product development strategy is an effort made by an institution to improve existing products, or by adding more varied and marketable products. In the product development strategy, BSI KCP Lamongan Pasar Babat uses a marketing strategy through promotion, monitoring developments carried out by competitors, the Door to Door strategy. promotions carried out by BSI KCP Lamongan Pasar Babat, namely through making brochures provided at the office and advertisements on the website, monitoring the development strategy carried out by competitors. Door to Door is a marketing effort of a product or service that goes directly to prospective buyers/prospective customers, in order to gain effectiveness in explaining the products/services we have.